2020
DOI: 10.1088/1361-665x/aba9e6
|View full text |Cite
|
Sign up to set email alerts
|

Electro-mechanical properties of thermoplastic polyurethane films and tubes modified by hybrid carbon nanostructures for pressure sensing

Abstract: Electrical and piezoresistive properties of hybrid nanocomposite films and tubes made of a segmented aliphatic polyurethane modified with multilayer graphene sheets (MLGSs), multiwall carbon nanotubes (MWCNTs), and hybrid mixtures of both, were investigated.Hybrid nanocomposites were fabricated at a total weight concentration ( ) of 5 wt.%, with relative weight concentration of MLGSs with respect to MWCNTs ( ) of 25%, 50% and 75%. The electrical conductivity of these films is dominated by the MWCNT network, ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…%) indicates the increasing influence of interfacial polarization, due to the differences between the conductivities and permittivities of the polymer and CNTs [42]. The transition frequency where the frequency-independent zone changes to a frequency-dependent one has been named 'critical frequency' ( f c ) [43,44]. Herein, such a critical frequency was calculated from the intersection of straight lines corresponding to fittings of the frequency-dependent and frequency-independent regions in the BDS spectrum.…”
Section: Broadband Impedance Spectroscopy Of Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…%) indicates the increasing influence of interfacial polarization, due to the differences between the conductivities and permittivities of the polymer and CNTs [42]. The transition frequency where the frequency-independent zone changes to a frequency-dependent one has been named 'critical frequency' ( f c ) [43,44]. Herein, such a critical frequency was calculated from the intersection of straight lines corresponding to fittings of the frequency-dependent and frequency-independent regions in the BDS spectrum.…”
Section: Broadband Impedance Spectroscopy Of Nanocompositesmentioning
confidence: 99%
“…Higher number of micro-capacitors increases the susceptibility of the material to polarization effects with increasing temperature [45,48], causing a decrease in the critical frequency for higher temperatures, as seen in figure 3(a). For frequencies lower than f c , polarization effects are still incipient so the majority of the micro-capacitors may behave like open circuits [42,44,48]. In this sense, it has been reported that MWCNT/PP nanocomposites below the electrical percolation threshold behave as highly polar dielectrics at temperatures below 80 • C, and present dielectric relaxation effects for f > 1 MHz [13].…”
Section: Effect Of Temperature In the Impedance Responsementioning
confidence: 99%
“…They reported that with the addition of 1 wt% CNT/GNP bifiller, the tensile strength and toughness became 1.9 and 2.9 times those of neat TPU, which was attributed to homogeneously distributed fillers and their unique energy dissipations. Pérez-Aranda et al 27 prepared bi-filler composite films of TPU containing multiwalled CNTs (MWCNTs) and multilayer graphene sheets at a total weight concentration of 5 wt% and investigated their electrical and piezoresistive properties. They reported that the electrical conductivity and pressure sensitivity factor of composites are dominated by the MWCNT network.…”
Section: Introductionmentioning
confidence: 99%
“…It can be expected that a strong interface coupling effect can take place between two nanostructures owing to the existence of affluent surface states. , In addition, QDs can form effective trap centers, and the filling of trap level is tunable. Therefore, some novel properties are likely to appear. , For carbon materials, they can generally show superior conductive properties, and furthermore, they can show a PZR effect as well. Therefore, it is more suitable as a matrix of a hybrid composite structure to build high-performance GPZR materials. For the nanostructure with one-dimension (1D), in addition, it is extremely beneficial to build a single nanostructure-based two-terminal device, and thus, it is very easy for the actual physical mechanism to be well-identified by the simple configuration in comparison with nanostructure assemblies. Accordingly, it is more appropriate for an individual 1D nanostructure to serve as a building block to directly construct a nanodevice.…”
Section: Introductionmentioning
confidence: 99%